Cryopreserved amniotic membrane in chronic nonhealing wounds: a series of case reports - Horvath, Vojtech; Svobodova, Alzbeta; Cabral, Joao Victor; Stadler, Petr; Lindner, Jaroslav; Mrstinova, Miluse Berka; Balogh, Lukas; Jirsova, Katerina (Cell and tissue banking, 2024)
A case series of the use of amniotic membrane (AM) for treating chronic nonhealing wounds. It presents five cases of polymorbid patients with a total of nine chronic nonhealing wounds. The patient group consisted of four men and one woman with various comorbidities, aged 45-72 years. The mean initial wound size was 15.8 cm2, and the mean time from the onset of the wound to the first application of AM was 122 weeks. The wounds were caused by chronic venous insufficiency and/or peripheral arterial disease. Wounds were treated in a standardized protocol. AM was applied weekly in the first month and then every two weeks. Photo documentation of the wound and microbiological colonization was carried out at each visit. In three out of five patients, the AM treatment effectively promoted healing up to complete wound closure. In two cases, the wounds stayed unhealed despite numerous AM applications. Pain relief was noted in all patients. The success of the treatment was closely tied to patient factors, such as adherence to the prescribed treatment regimen and individual patient characteristics. In some cases, treatment failure was observed, possibly due to underlying comorbidities, wound parameters, or poor patient compliance. AM treatment has the potential to become a viable treatment option for these nonhealing wounds. However, the effectiveness of the treatment may be influenced by various patient factors and the underlying cause of the wound. Therefore, it is crucial to have an individualized treatment plan that considers these particular factors.
Keywords: hojení ran; kryoprezervace; Peripheral artery disease; Humans; Cryopreservation; Female; výsledek terapie; lidé; Chronic nonhealing wound; Wound Healing; Cryopreserved amniotic membrane; ženské pohlaví; Male; Retrospective Studies; Treatment Outcome; Amnion; Chronic venous insufficiency; retrospektivní studie; Wound healing; mužské pohlaví; amnion